SISTEM INFORMASI PELAPORAN KEUANGAN PADA CAFE COFFEEGRAPHER - Tirza Nurul Ramadhani; Afifah; Junaedy (KHARISMA Tech, 2021)
This research aims to design a financial reporting information system at the Coffeegrapher Cafe that is able to present financial reports in accordance to accounting standards to facilitate café coffee owners in making financial reports. In this financial reporting information system using General Journal, Ledger and Balance Sheet as a transaction process to find out the desired destination. In the modeling phase using detailed diagrams, then implemented using the Visual Basic 6.0 programming language and MySQL as the database. Furthermore, testing on this system uses the Black Box testing method. The results of this research are financial reports at the Coffeegrapher Café.